Mengungkap Praktik Akuntansi Budaya Dalam Upacara Adat Pelantikan Orang Kay Suku Kei Maluku - Syifaatuz Zadida Ilyas Syifa; Ana Sopanah; Dwi Anggarani; Khojanah Hasan (Politeknik Ganesha Medan, 2023)
This study aims to uncover accounting practices in financing the traditional ceremony of the inauguration of the traditional head (Orang Kay) in the Kei Tribe. The research uses an ethnomethodological approach with observation, interview, and documentation methods. Based on the results of interviews and data analysis, in the inauguration of the traditional head (Orang Kay) there is an accounting practice that has characteristics with other tribes. In the inauguration of Orang Kay, there are three sources of financing, namely Yelim, village funds, and city government grants. The allocation of yelim is used to finance the inauguration traditionally, while the allocation of village funds and government grants is used as financing for the inauguration in government. In yelim management there